EFFECT OF GRAZING، FEEDING FREQUANCY AND HORMONAL TREATMENT ON SOME PRODUCTIVE AND PHYSIOLOGICAL PARAMETERS IN AWASSI EWES DURING PREGNANCY PERIOD - Saeb Abdul-Rahman; Rathi Abdullah; Khalid Sultan (Mesopotamia Journal of Agriculture)
Eighty Awassi ewe lambs(10 month aged) were used to evaluate the effect of Grazing GR, Feeding frequency FF and hormonal treatment HT on, as Body weight BW and Body gain BG. Glucose GL, Total protein TP, Albumin ALB, Globulin GLO, Triglycerides TG and Blood urea BU. Estrous synchronization was conducted, Animal groups (10 ewes each), 8 different treatments were applied including GR, FF, eCG and GnRH hormonal treatments. Results showed a significant increase (p<0.05) in BW in GR groups at 1st 2nd month of pregnancy and in the group that rationed once daily at the 1st , 2nd and 3rd month of pregnancy, while the best interaction effect on BW was recorded in T1 and T2 at the 1st , 2nd and 3rd month. There was a significant increase in BG in the groups rationed twice daily at 4th month, while the interaction effect on BG was recorded in T5 at the 3rd month and T7 at the 4th month. GR, FF and HT had no significant effects on biochemical parameters at 1st and 5th month of pregnancy, except a significant increase by the interaction in TG in T1 as compared with T2 at the 1st month. Comparing the results of 1st and 5th month showed there are a significant increase in GL, GLO and BU and a significant decrease in ALB and TG at the 5th month of pregnancy. In conclusion, the study revealed that GR and FF affect BW of the early stages of pregnancy and this effect disappeared at the late period, GL, GLO and BU increased, ALB and TG decreased with the progress of pregnancy period in Awassi ewes.